Older Adults: Understanding of Nutrition - Morais, Cecília (2021)
Objective: The aim of this study was to: 1) explore older patients knowledge, skills and behavior in relation to nutrition and 2) achieve an understanding of older patients experiences, understanding and attitudes towards management of nutritional needs. Design: Semi-structured interviews were conducted and analyzed using content analysis. The Readiness and Enablement Index for Health Technology (READHY) instrument was used as a framework. Setting: Two hospital units specialized in internal medicine located at two university hospitals in Copenhagen. Participants: Patients (N = 25) age 65 years and admitted to hospital for medical treatment. Findings: The informants knowledge, behavior and attitude towards nutrition was influenced by their experience of food as an everyday phenomenon but less so by the experience of nutrition as important for their well-being and health. Three themes were identified: 1) Food an everyday phenomenon; 2) Habits and preferences and 3) When food becomes nutrition. Conclusion: Older, ill patients have limited knowledge about specific needs for energy and protein and the importance of nutrition for their physical functioning. They have potential resources and competencies which can positively impact and be utilized in nutritional interventions. Social interaction, the pleasurable experience of eating well-prepared food, and daily routines facilitate their nutritional intake.